Mathematics for young children : An active thinking approach - Bird, Marion H. (London : New York : Routledge, 1991)
Using case studies and examples of children's work, this study shows how children of all abilities can be encouraged to carry out their own mathematical explorations whilst at the same time covering the prescribed elementary curriculum.
Includes bibliography references, index and notes.
Keywords: Great Bratain Primary schools; Mathematics -- study and teaching (Elementary).